Congestion in onboarding workers and sticky R&D - Justin Bloesch; Jacob P. Weber (Federal Reserve Bank of New York, 2023)
R&D investment spending exhibits a delayed and hump-shaped response to shocks. We show in a simple partial equilibrium model that rapidly adjusting R&D investment is costly if the probability of converting new hires into productive R&D workers ("onboarding") is decreasing in the number of new hires ("congestion"). Congestion thus causes R&D-producing firms to slowly hire new workers in response to good shocks and hoard workers in response to bad shocks, providing a microfoundation for convex adjustment costs in R&D investment. Using novel, high-frequency productivity data on individual software developers collected from GitHub, a popular online collaboration platform, we provide quantitative evidence for such congestion. Calibrated to this evidence, a sticky-wage new Keynesian model with heterogeneous investment-producing firms subject to congestion in onboarding and no other frictions yields hump-shaped responses of R&D investment to shocks.
Keywords: E22; O36; 330; intangibles; monetary policy; R&D; innovation; team specific capital; labor adjustment costs